BE_ZIVILSTRAF BK 2017 381 vom 20. Dezember 2017 - BE Obergericht (2017)
Einstellung/Nichtanhandnahme Strafverfahren wegen Tätlichkeiten, Drohung, übler Nachrede und Vergewaltigung | Einstellung/Nichtanhandnahme